Sexual Behaviour among Higher Secondary School Students of Kathmandu Metropolitan City - Khanal, P (Health Prospect, 2018)
Background:Lack of knowledge and skills to avoid risky behaviour and lack of access to youth- friendly reproductive health information and services place young people in a position of great vulnerability.Adolescents are at the stage of experimentation and are easily influenced by their peers and are therefore a vulnerable population at risk for HIV/ AIDS and other STIs. Safe sexual behaviour has a crucial role in the prevention of problems related to sexual and reproductive health. The study was designed to explore the sexual behaviour among students of Higher Secondary School in Kathmandu Metropolitan City. Methods: The study was cross-sectional and a total of 268 students enrolled in 12th grade from 6 Higher Secondary Schools were involved in the data collection process. Data collection was done using anonymous, self-administered questionnaire Results: Among total 263 unmarried students, nearly onefifth (17.9%) students have ever had sexual contact. Study showed that nearly half of the sexually experienced students (46.8%) were involved in unsafe sexual behaviour. Conclusion: Nearly one-fifth students had premarital sex and nearly half of the students had been involved in unsafe sexual behavior. Based on the findings, the study recommends that the major concern should be on making the sexual relations safe and it is therefore necessary to encourage young people to be consistent condom users. DOI: http://dx.doi.org/10.3126/hprospect.v11i0.7424 Health Prospect 2012;11:15-18